Synthesis of 25-(Thioalkyl-alkoxy)-p-tertbutylcalix[4]arene in One Reaction System - Cao*, Bingqing; Huang, Qibin; Qing, Molin (Asian Journal of Chemistry, 2014)
25-(Thioalkyl-alkoxy)-p-tertbutylcalix[4]arene with self-assembled monolayers character was synthesized by two steps nucleophilic substitute reaction in NaH-THF phase with p-tertbutylcalix[4]arene and dibromodecane. The structure of product was characterized by FT-IR, 1H NMR, 13C NMR and MALDI-TOF-MS.